Transition Of Authority Judicial Institutions Simultaneous National Elections 2024 - Salahudin Pakaya; Roy Moonti; Yusrianto Kadir; Taufik Firmanto (CV. AFDIFAL MAJU BERKAH, 2023)
The decision of the Constitutional Court No. 97/PUU-XI/2013 resulted in changes in the function and authority of the judicial institution that adjudicates Pilkada. The Constitutional Court's decision then gave birth to Article 157 of Law No. 10 of 2016 Amending Law No. 8 of 2015 (Pilkada Law) which contains provisions for the establishment of a special election judicial body that will hear disputes over the results of simultaneous national elections in 2024. However, the establishment of a special election judicial body mandated by the Pilkada Law still faces juridical obstacles if it is linked to Law 48 of 2009 concerning Judicial Power, and laws governing judicial bodies under the auspices of the Supreme Court, especially the general and state administrative courts. Another juridical problem is the Constitutional Court Decision Number 85/PUU-XX/2022 which states that the phrase